UPAYA MENINGKATKAN KUNJUNGAN WISATAWAN DI RESORT PENTADIO KECAMATAN TELAGA BIRU KABUPATEN GORONTALO - Desrika Talib (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2019)
Resort pentadio is one of the tourism objects found in Gorontalo province. It has a tourism product that can meet the diverse needs of beriwisata. It has the diverse products of tourism that can service the tourist’s need. The decrease of quantity of tourism visitors every year at Resort pentadio become a serious problems and this must be resolved. More the similar tourism business found in Gorontalo demand the plan of marketing strategy effectively. Therefore, this study is dealing with the creativity of getting the alternative strategies in promoting and marketing the tourism place Resort Pentadio. The result of research is found that there are several strategies alternatively that can be used at Resort Pentadio in Gorontalo Regency, namely : to recruit a potential employee, to conduct training to the employee regularly by marketing experts, providing motivation for employees by employees who are unable or potentially will be rewarded, to carried out promotional activities in order to attract tourists to visit, to conduct collaboration and cooperation with the media such as TV, radio, leaflet, internet in order to promote Resort Pentadio, so that tourists are interested in visiting it; to create the natural environment comfortable, enjoyable, romantic; therefore they are probably to stay a long time and a long day